Mental health impact of COVID-19 on healthcare workers versus adults in Africa - Mutshidzi Mulondo; Sithembiso Ndlovu; James Ndirangu; Joyce Tsoka-Gwegweni (AOSIS, 2024)
Background: This review mapped the impact of the coronavirus disease 2019 (COVID-19) pandemic on the mental health of healthcare workers (HCWs) and the adult general population in Africa. Aim: The study focussed on anxiety, depression, post-traumatic stress disorder and suicide cases to determine the impact of COVID-19 on the mental health of the selected population. Method: A scoping review was conducted on relevant database and search engines. The search resulted in 143 studies. Five studies met the inclusion criteria for synthesis. Results: Results indicated anxiety was more prevalent among HCWs as opposed to the adult general population, which was in the rise of suicide cases. Among HCWs, mental health was negatively impacted by the loss of their infected patients and concerns over infecting family members. The adult general population was impacted because of isolation and their fear of contracting the virus. Conclusion: The COVID-19 pandemic led to the increase of mental health issues among HCWs as evidenced by a high prevalence of anxiety compared to that of the adult general population. There was, however, a rise in depression and suicide cases among the adult general population. Contribution: This study will assist in adding more knowledge to build a robust and responsive strategy to mental health problems during and post-pandemics like COVID-19. Strategies that have appeared effective in combatting the impact of COVID-19 on mental health include support packages established for frontline HCWs such as social media online chat groups.